The Correlation between Learning Style and English Learning Outcome at First Grade Students SMA PGRI 2 Jambi in Academic Year 2018/2019 - Sonnauli Hutagalung; Wennyta Wennyta (Universitas Batanghari Jambi, 2020)
This study aimed to investigate the correlation between learning style and English learning outcome ay first grade students SMA PGRI 2 Jambi in academic year 2018/2019. This study had 28 students as participants in this current research and they were taken from 5 classes (X MIA 1, X MIA 2, X IIS 1, X IIS 2 and X IIS 3). This study uses survey method by using questionnaire which is adopted from The Barsch Learning Style Inventory as cited from NZESEI (2015) as the instrument of the research. The questionnaire itself consists of 24 statements containing 3 sub variables of learning strategies known as VAK (Visual, Auditory and Kinesthetic respectively). The coefficient correlation was analyzed by using SPSS 16 program. The result of this study found out that there was a negative correlation between learning strategies and learning outcome (r=-.417, p<05). From the three parallel constructs, there were none them correlated with English learning achievement; auditory (r=-.383, p<0.5), kinesthetic (r= -411, p<05), while for visual did not correlate (at p<0.5) with English learning achievement. Therefore, it can be concluded that there was no correlation between students’ learning strategies and the English learning outcome itself among the first graders at SMA PGRI 2 Jambi in academic year 2017/2018. For the sake of more varied results, it is suggested for the future related research to use different data collection technique (e.g: using, interview, observation and etc.) and has a bigger number sample. Next, since this present study is not done in such a long time, so further and future research can be conducted in a relatively longer time.Key words: Learning Style, Learning Outcome, English Learning Achievement.